(3GdeMGSHI GdMchejI hGdbhejIs - (3UdGM GdOjf YHO GdefYe(B, (3eHGQcs ((3GdEScfOQjI(B:s (3ecJHI GdhaGA GdbGfhfjI(B,s, 2013)
(3jVe GdeMGSHI GdMchejI, GdEWGQ GdfXQj ddeMGSHI GdMchejI, GdehGRfI GdYGeI ddOhdI, gjcd fXGe GdeMGSHI, GdeMGSHI Yf GdehGQO GdeMGSHI ef GdESJNOeGJ, GdJbGQjQ GdOhQjI hGdMSGH GdNJGej GdSfhj ddOhdI, eMGSHI GdJcGdja aj GdeTQhYGJ GdNOeGJ GdYGeI , GdeMGSHI GdbhejI, GdEWGQ GdfXQj ddeMGSHI GdbhejI, fXGe GdMSGHGJ GdbhejIs
Keywords: (3GdeMGSHI GdMchejIs; (3GdeMGSHI GdbhejIs; (3GdejRGfjI GdYGeIs; (3JObjb GdMSGHGJ GdMchejIs